The ECB's tracker: Nowcasting the press conferences of the ECB - Armando Marozzi (European Central Bank (ECB), 2021)
This paper proposes an econometric framework for nowcasting the monetary policy stance and decisions of the European Central Bank (ECB) exploiting the ow of conventional and textual data that become available between two consecutive press conferences. Decompositions of the updated nowcasts into variables' marginal contribution are also provided to shed light on the main drivers of the ECB's reaction function at every point in time. In out-of-sample nowcasting experiments, the model provides an accurate tracking of the ECB monetary policy stance and decisions. The inclusion of textual variables contributes signifi- cantly to the gradual improvement of the model performance.
Keywords: E37; E47; E52; 330; Natural Language Processing; Dynamic Factor Model; Monetary Policy; Forecasting